Reinforced glass-ceramics: Parametric inspection of three-dimensional wear and volumetric loss after chewing simulation - Tribst, João Paulo Mendes [UNESP]; Alves, Larissa Marcia Marques [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; de Melo, Renata Marques [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Paes-Junior, Tarcísio José Arruda [UNESP]; Bottino, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2019)
The aim of this study was to investigate the three-dimensional wear, volumetric loss and surface roughness after chewing simulation of two glass ceramics. Lithium disilicate (LD, Emax CAD, Ivoclar) and Zirconia reinforced lithium silicate (ZLS, Vita Suprinity, Vita Zhanfabrick) discs (n=20/g) were scanned to obtain stereolithography (STL) files for each sample. All discs were submitted to chewing simulation with sliding configuration (30 N, 300,000 cycles, 6 mm and 1.7 Hz) with steatite as antagonist. The samples were then scanned again and the volume loss and the deepest defect depth was measured using the superimposed file from the baseline using three-dimensional digital parametric inspection software (GOM Inspect, Braunschweig, Germany). Surface roughness (Ra and Rz) was analyzed with a contact profilometer. Data were analyzed by one-way ANOVA and Tukey test (α=0.5%). ANOVA showed significant differences among the groups. Considering the ceramic volume loss, wear depth defect length and Rz roughness, LD (-22.09±5.57%; 0.80±0.06 µm; 3.08±1.02 µm) showed higher mean values than ZLS (-15.67±4.51%; 0.56±0.09 µm; 1.51±0.90 µm). Ra mean values were similar for both materials (p=0.064). All discs exhibited slight surface scratches along with the sliding direction with pitted wear patterns, while large cracks were observed on wear traces. These same areas can be identified in blue, overlapping the STL files before and after chewing simulation in inspection software. The linear reduction generated by sliding contact shows a graph with a similar wear pattern shape. ZLS was more resistant to wear than LD, with less volume loss and shallower surface defects.
Keywords: Ceramics; Volume loss; Wear simulation